Cell-type-specific role of P2Y2 receptor in HDM-driven model of allergic airway inflammation - Schneble, Dominik; El-Gazzar, Ahmed; Kargarpour, Zahra; Kramer, Markus; Metekol, Seda; Stoshikj, Slagjana; Idzko, Marco (Frontiers in Immunology, 2023)
Allergic airway inflammation (AAI) is a chronic respiratory disease that is considered a severe restriction in daily life and is accompanied by a constant risk of acute aggravation. It is characterized by IgE-dependent activation of mast cells, infiltration of eosinophils and activated T-helper cell type 2 (Th2) lymphocytes into airway mucosa. Purinergic receptor signaling is known to play a crucial role in inducing and maintaining allergic airway inflammation. Previous studies in an ovalbumin (OVA)-alum mouse model demonstrated a contribution of the P2Y2 purinergic receptor subtype (P2RY2) in allergic airway inflammation. However, conflicting data concerning the mechanism by which P2RY2 triggers AAI has been reported. Thus, we aimed at elucidating the cell-type-specific role of P2RY2-signaling in house dust mite (HDM)driven model of allergic airway inflammation. Thereupon, HDM-driven AAI was induced in conditional knockout mice, deficient or intact for P2ry2 in either alveolar epithelial cells, hematopoietic cells, myeloid cells, helper T cells or dendritic cells. To analyze the functional role of P2RY2 in these mice models, flow cytometry of bronchoalveolar lavage fluid (BALF), cytokine measurement of BALF, invasive lung function measurement, HDM re-stimulation of mediastinal lymph node (MLN) cells and lung histology were performed. Mice that were subjected to an HDM-based model of allergic airway inflammation, resulted in reduced signs of acute airway inflammation including eosinophilia in BALF, peribronchial inflammation, Th2 cytokine production and bronchial hyperresponsiveness in mice deficient for P2ry2 in alveolar epithelial cells, hematopoietic cells, myeloid cells or dendritic cells. Furthermore, the migration of bone marrow-derived dendritic cells and bone marrow-derived monocytes, both deficient in P2ry2, towards ATP, was impaired. Additionally, we found reduced levels of MCP-1/CCL2 and IL-8 homologues in the BALF of mice deficient in P2ry2 in myeloid cells and lower concentrations of IL-33 in the lung tissue of mice deficient in P2ry2 in alveolar epithelial cells.In summary, our results show that P2RY2 contributes to HDM-induced airway inflammation by mediating pro-inflammatory cytokine production in airway epithelial cells, monocytes and dendritic cells and drives recruitment of lung dendritic cells and monocytes.